Alaska's Changing Boreal Forest - Chapin, F. Stuart (Francis Stuart); III (Long-Term Ecological Research Network series, 2006)
The boreal forest is the northern-most woodland biome, whose natural history is rooted in the influence of low temperature and high-latitude.Alaska's boreal forest is now warming as rapidly as the rest of Earth, providing an unprecedented look at how this cold-adapted, fire-prone forest adjusts to change.